The Military Orders. Vol. 6.1, Culture and Conflict in the Mediterranean World, and Vol. 6.2, Culture and Conflict in Western and Northern Europe - Maleszka, Anna (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2018)
The Military Orders. Vol. 6.1, Culture and Conflict in the Mediterranean World, and Vol. 6.2, Culture and Conflict in Western and Northern Europe Edited by Jochen Schenk and Mike Carr. London–New York: Routledge/Taylor & Francis, 2017. 228 and 241 pp. ISBN: 978-1-4724-7635-7 and 978-1-4724-7638-8.